An inherently flame-retardant polyamide containing a phosphorus pendent group prepared by interfacial polymerization. Issue 85 (30th August 2016) - Ge, Hua; Wang, Wei; Pan, Ying; Yu, Xiaojuan; Hu, Weizhao; Hu, Yuan
Abstract : Inherent flame retardation has the advantage that it will allow polymers to impart the flame retardancy permanently, and the introduction of a few weight percent of the flame retardant unit can lead to improvements in the overall flame retardancy. Abstract : Inherent flame retardation has the advantage that it will allow polymers to impart the flame retardancy permanently, and the introduction of even a few weight percent of the flame retardant unit can lead to remarkable improvements in the overall flame retardancy. In this paper, DDP was acyl-chlorinated as the monomer to synthesise the inherent flame-retardant polyamide by interfacial polymerization. Then, the chemical structures, crystalline structures, molecular weight, thermal properties, thermal stabilities and flame retardancy of the resultant polyamides were studied. The results show that the inherent flame-retardant polyamide has good thermal stability, T d of the samples were all above 310 °C. Furthermore, the incorporation of DDP, just 7.5 mol%, into the molecular chain can significantly improve the flame retardancy of polyamide, causing the pHRR value to be reduced by 37.8%.